¡Que se vaya la escoria! Subexposición y ritos de institución sobre el migrante cubano en las fotografías del periódico Granma - Jenny Macías Chaveco (Confluenze, 2022)
This article analyzes some of the photographs that appeared in the Granma newspaper during the Mariel crisis in 1980, and their uses in the characterization and negative institution of the Cuban migrant. The theoretical axes are the category "institutional rites" proposed by Pierre Bourdieu, and the "underexposure" worked by George Didi-Huberman. The study reflects on the role of the press image, allied to power, and its strategies to construct representations of the subjects that generate positions and social behaviors towards them.